2012
DOI: 10.1016/j.biopsych.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Transcranial Magnetic Stimulation Targets for Depression Is Related to Intrinsic Functional Connectivity with the Subgenual Cingulate

Abstract: BACKGROUND Transcranial magnetic stimulation (TMS) to the left dorsal-lateral prefrontal cortex (DLPFC) is used clinically for the treatment of depression. However the antidepressant mechanism remains unknown and its therapeutic efficacy remains limited. Recent data suggests that some left DLPFC targets are more effective than others, however the reasons for this heterogeneity and how to capitalize on this information remain unclear. METHODS Intrinsic (resting state) fMRI data from 98 normal subjects were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

62
888
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 914 publications
(995 citation statements)
references
References 70 publications
62
888
1
10
Order By: Relevance
“…This concept can potentially be used to predict treatment outcome or to increase treatment efficacy of repetitive stimulation of the DLPFC in MDD. For example, by targeting treatment at the functional region near the DLPFC that leads to individual sgACC activation, assuming the pathway from prefrontal cortex to sgACC is the mechanism of action of the antidepressant effect of rTMS, as has been suggested (Baeken et al, 2014; Fox et al, 2012). In this way, future studies can investigate whether propagation of TMS‐induced activity to sgACC is an accurate predictor of a clinical response to rTMS treatment of the DLPFC in a clinical population of patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concept can potentially be used to predict treatment outcome or to increase treatment efficacy of repetitive stimulation of the DLPFC in MDD. For example, by targeting treatment at the functional region near the DLPFC that leads to individual sgACC activation, assuming the pathway from prefrontal cortex to sgACC is the mechanism of action of the antidepressant effect of rTMS, as has been suggested (Baeken et al, 2014; Fox et al, 2012). In this way, future studies can investigate whether propagation of TMS‐induced activity to sgACC is an accurate predictor of a clinical response to rTMS treatment of the DLPFC in a clinical population of patients with MDD.…”
Section: Discussionmentioning
confidence: 99%
“…This can be done by using a patient's individual response to TMS to optimize the effects after subsequent treatment with repetitive stimulation. More specifically, identification of the propagation patterns can reveal whether TMS‐induced activity evoked at the DLPFC has the ability to propagate to the sgACC, and potentially modulate the activity in the sgACC (Fox et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Repetitive TMS has also been used to modulate the activity of local brain regions implicated in a range of psychiatric and neurological disorders. For example, rTMS-induced enhancement or reduction of neural activity within the left dorsolateral prefrontal cortex (DLPFC) can reduce symptoms of depression, schizophrenia, anxiety, and post-traumatic stress disorder (Prikryl et al, 2007;Fitzgerald et al, 2009;Fox et al, 2012;Balconi and Ferrari, 2013). Of note, though, is that a recent meta-analysis has suggested that the efficacy of this local approach is probably suboptimal (Lefaucheur et al, 2014).…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Although several reviews have alluded to the effects of NIBS propagating to distant regions via axonal connectivity (Lefaucheur et al, 2014;Liew et al, 2014;Li et al, 2015), they have not considered the consequence of these aspects in the clinical domain. An often overlooked factor affecting the effectiveness of NIBS is the optimal targeting of underlying neural networks associated with the clinical condition (Fox et al, 2012). For instance, the efficacy of TMS in the treatment of depression is influenced by the precise location of stimulation within the DLPFC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation